EMPOWERING YOUNG LEARNERS: TALKING STICK WITH QUESTION BOX MEDIA TO BOOST MATHEMATICS ACHIEVEMENT - Nial, Putri; Firdaus, Andi Mulawakkan; Ernawati (Almeera Education, 2025)
This study investigates the effect of the Talking Stick learning model supported by Question Box media on third-grade students’ mathematics achievement at SDN 65 Pajalesang, Palopo City. Employing a pre-experimental One-Group Pretest-Posttest Design with 23 participants, the research utilized mathematics achievement tests, observation sheets, and response questionnaires. Findings revealed a significant improvement in learning outcomes, with average scores rising from 50.00 to 80.52 and an N-Gain of 0.4354 (moderate category). The Wilcoxon Signed Rank Test indicated a significance value of < 0.001, confirming a substantial difference before and after treatment. Students also demonstrated increased motivation, activeness, and confidence in learning. The novelty of this study lies in integrating the Talking Stick model with Question Box media to stimulate active participation and comprehension. The results contribute to innovative mathematics pedagogy by demonstrating an effective, engaging approach to improving elementary students’ learning outcomes.